2005
DOI: 10.1159/000087680
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Tracheal Imaging by Optical Coherence Tomography

Abstract: Background: Optical coherence tomography (OCT) is a new technology capable of generating high resolution cross-sectional images of complex tissue in real time. Analogous to ultrasound, OCT measures backscattered light intensity using coherence interferometery to construct topographical images of complex tissue. Since OCT uses infrared light rather than acoustic waves, its spatial resolution is exceptionally high (2–10 µm). Recent advances in data acquisition, analysis, and processing enable real-time imaging, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 22 publications
3
28
0
2
Order By: Relevance
“…(5,13) Imaging with OCT can be performed in a few minutes, as part of conventional bronchoscopy. In addition, during the same procedure, it is possible to perform bronchoalveolar lavage, endobronchial biopsy, and dynamic inspection.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(5,13) Imaging with OCT can be performed in a few minutes, as part of conventional bronchoscopy. In addition, during the same procedure, it is possible to perform bronchoalveolar lavage, endobronchial biopsy, and dynamic inspection.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the penetration depth is still limited (approximately 3 mm), and the imaging catheter is very fragile and has a reduced diameter, requiring extremely careful handling. (4,5,14) There are several ongoing clinical studies aimed at determining the usefulness of OCT in characterizing normal tissue and differentiating diseases. Ophthalmology is the medical specialty in which OCT is most commonly used, OCT being a valuable tool in the diagnosis and clinical follow-up of macular edema, choroidal neovascularization, and glaucoma-related changes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Its current use in the respiratory system is limited: research to date has focused on detection of dysplastic and neoplastic epithelial changes. Airway validation studies using explanted animal and human airways have been performed and demonstrate near-histological resolution [88][89][90]. A recent study by COXSON et al [91] used OCT to measure airway lumen and wall area in 44 current and former smokers.…”
Section: Optical Coherence Tomographymentioning
confidence: 99%
“…High-resolution flexible fiber optic optical coherence tomography (OCT) provides the potential to observe real-time changes in the airway mucosa and epithelium using minimally invasive imaging techniques. [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] Most importantly, some of the early pathologic changes following smoke inhalation that may be indicative of the extent of injury such as edema and hyperemia 2,[26][27][28][29] may not be apparent clinically, endoscopically, or following histologic preparations of excised specimens, but can be readily detected on OCT. 30 Previous OCT airway injury studies 30 in rabbit smoke inhalation models suggested to us that the upper trachea airway may react very differently to acute smoke inhalation compared to distal trachea and proximal bronchi. The purpose of this study was to demonstrate the potential role of OCT in quantitatively detecting early smoke inhalation injury and assessing differences in response of more proximal versus distal large airways to smoke inhalation injury.…”
Section: Introductionmentioning
confidence: 99%